Effect of thermal treatment of a clay-based raw material on porosity and thermal conductivity: experimental approach, image processing and numerical simulation. Issue 10 (3rd October 2017) - Buncianu, D.; Tessier-Doyen, N.; Courreges, F.; Absi, J.
Abstract : This work aims to reveal the influence of thermal treatment on thermal conductivity of a clay-based raw material. The analysis of the effect of the porous network and solid skeleton on thermal conductivity has been performed by numerical simulation. Three steps were combined: (i) elaboration, (ii) characterisation, (iii) validation and comparison with experimental results. In filigree, the objective is to make an insulating material for the building field while decreasing energy of fabrication. After the step of elaboration, the porosity was evaluated experimentally by pycnometer and mercury intrusion porosimeter and numerically by means of micrographs observations. The effective thermal conductivity was evaluated using the laser flash technique and compared to results obtained by numerical simulation using ABAQUS software. The influence of the microstructure characteristics was highlighted by the numerical study which enables to overcome the limitation of the classical analytical models. As results, we observe that when the temperature of fabrication decreases of about 200 °C, the pore volume fraction is multiplied by six while the thermal conductivity decreases four times. The mechanical properties remain acceptable for a construction field. These tendencies were confirmed by both experimental and numerical approaches.